Strategic Utilization of Ibda’ Magazine as an Innovative Instructional Medium to Enhance Students’ Arabic Reading Skills - Zulpina, Zulpina; Lazuardi, Achmad Makki; Hanifansyah, Nur; Marjuni , Kamaluddin Nurdin (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2025)
This study investigates the strategic utilization of Ibda’ Magazine as an innovative instructional medium to enhance Arabic reading skills (maharah qirā’ah) among students in a pesantren-based educational environment. Employing a mixed-methods approach, the study was conducted at Pondok Pesantren Darullughah Wadda’wah and involved 120 senior secondary students across four intact classes. Ibda’ Magazine (Edition 3) was integrated into the curriculum through structured strategies such as pre-reading prediction, guided reading, mnemonic reinforcement, post-reading reflection, and Jigsaw collaboration. Quantitative data revealed significant gains across three reading domains: vocabulary retention (from 63.5 to 83.2), inferential comprehension (from 60.1 to 75.4), and identification of main ideas (from 63.2 to 77.9), with a mean increase from 62.3 to 78.9 (p < 0.001). Qualitative findings from interviews and reflections showed enhanced student motivation, contextual understanding, and ownership of learning. The study concludes that Ibda’ Magazine promotes both reading proficiency and learner identity, serving as an authentic, culturally responsive medium in Arabic language pedagogy.